“Video Killed the Radio Star”: Transitioning from an Audio- to a Video-Based Exam in Hungarian Language Classes for International Medical Students - Gabriella Hild; Anna Dávidovics; Vilmos Warta; Timea Németh (Education Sciences)
This action research examines the transition from audio- to video-based tasks in the final Medical Hungarian exam for international medical students, aiming to better align assessment with real-life language needs and enhance student motivation. Conducted at a Hungarian medical university with 61 second-year students, the study uses a mixed-methods approach. Quantitative data from a questionnaire and qualitative insights from focus group interviews reveal students’ experiences with the video-based exam tasks and preparatory materials. The results indicate a positive reception of the Practice Test Book and the new video exam format, with visual cues like body language aiding in comprehension and engagement. Students found that the video-based tasks closely mirrored clinical interactions, strengthening the relevance of language skills in professional contexts. Preparatory materials, including lead-in exercises, were well-received by students and seen as effective in improving readiness for the exam. The study suggests that the shift from audio- to video-based assessment can bridge classroom learning with real-world application, potentially serving as a model for other non-traditional study abroad settings in Languages Other Than English (LOTEs), especially as purely audio-based communication has become less prevalent in today’s world.